Examining the relationship between service quality and customer satisfaction: A factor specific approach - Azman Ismail; Ahmad Azan Ridzuan; Nur Ilyani Ranlan Rose; Muhammad Madi Bin Abdullah; Muhammad Sabbir Rahman; Sebastian K. Francis (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This research was aimed at examining the relationship between service quality and customer satisfaction with data obtained from Malaysian soldiers who were involved in peace keeping missions in a Middle Eastern country. The results of which would enable the management to improve the quality of service accorded to peacekeeping personnel. Design/methodology/approach: The study employed a cross-sectional research design which allowed the researchers to integrate the service quality literature, the semi structured interview and the actual survey to collect and examine the data for optimum results. Findings and Originality/value: The outcome of multiple regression analysis showed that responsiveness and assurance variables reflected a high correlation with customer satisfaction. On the other hand, tangibility, reliability and empathy variables recorded an insignificant correlation with customer satisfaction. Research limitations/implications: With respect to practical contributions, the findings of this study can be used as a guideline by the management to improve the quality of peacekeeping in areas of conflict. Practical implications: For security reasons, certain information affecting customer satisfaction could not be examined in detail. Originality/value: This paper presents key results on service quality and customers satisfaction research by looking at the niche segment which was not previously studied from the Malaysian perspective.
Keywords: 650; service quality; customer satisfaction; Malaysian soldiers